Essentials of oral communication towards effective and responsible speech - Valdez, Suzette F.; DelaCruz, Rommel B.;Alejo, Rosemarie D. (Intramuros, Manila, Philippines : Purely Books Trading and Publishing Corporation, 2013)
"Favoring more functionality and communicability over accuracy, this book acquaints the learners with English speech with the principal goal of making them confident and comfortable in its use. It intends them to develop fluency in ESL speech."--from the book
UNIT I: The Communication Process -- Chapter 1. Understanding the Concept of Communication -- Chapter 2. Components and Processes of Communication -- Chapter 3. Developing Speech Voice -- UNIT II: Types of Communication -- Chapter 4. Verbal communication -- Chapter 5. Nonverbal Communication -- Chapter 6. Financing Personal and Social Communication -- UNIT III: The Speaking Process -- Chapter 7. The English Speech Segments -- Chapter 8. The English Speech Suprasegmentals -- UNIT IV: Essential Steps in Speech Preparation -- Chapter 9. Speech Purpose, Audience and Body Language -- Chapter 10. Speaking with Courage and Wit -- UNIT V: Speech Outline and Delivery -- Chapter 11. Writing a Speech Outline -- Chapter 12. Delivering an Effective and Responsible Speech.
Includes bibliographical references.
Keywords: ORAL COMMUNICATION